Association between daytime sleepiness and motor vehicle accidents among Japanese male taxi drivers - Eisuke Takeyama; Kiyohide Tomooka; Hiroo Wada; Setsuko Sato; Noriko Sakiyama; Ryutaro Shirahama; Takeshi Tanigawa (IATSS Research, 2023)
Although the Epworth Sleepiness Scale (ESS) is a scoring system commonly used to assess daytime sleepiness (DS), the association between ESS and motor vehicle accidents (MVAs) remains unclear. Therefore, we conducted a cross-sectional study to examine the association between an increase in the Japanese version of the ESS (JESS) scores and MVAs among Japanese male taxi drivers. The study participants were 1384 Japanese male taxi drivers. DS was assessed using the JESS, and the total JESS scores were categorized into quartile groups. MVA experience during the past five years was assessed using a self-administered questionnaire. A multivariable generalized linear model was used to examine the association between JESS and MVAs after adjusting for age, body mass index, smoking status, snoring, sleep duration, driving experience, driving distance per year, hypertension, and diabetes mellitus.The proportion of MVAs was 59.7%. The multivariable-adjusted prevalence ratio (95% confidence interval) of MVAs for the highest quartile of the JESS score was 1.16 (1.04–1.29) compared to the lowest quartile, and for continuous JESS score was 1.01 (1.002–1.02). Thus, we found a significant association between an increase in JESS scores and MVAs among Japanese male taxi drivers after adjusting for potential confounders. Stratification by sleep duration and snoring status revealed a significant association among long sleepers and non-snorers. Our findings suggest that ESS evaluation methods be reconsidered in relation to MVA among commercial drivers.